Discourse Functions of Code-Switching among Normal Kannada-English & Malayalam-English Bilinguals – A Pilot Study - Medha Hegde; Deepthi Alva; Susan G.Oommen; Sapna Bhat (Journal of All India Institute of Speech and Hearing, 1970)
Code-switching is a complete shift to other language for a word, a phrase, a sentence and an utterance or borrowing a word from the other language and integrating it into the base language. Munhoa (1997) studied pragmatic functions among normal Basque-Spanish bilinguals and concluded that Basque-Spanish bilinguals use code-switching for a wide variety of purposes, from the need to fill lexical gaps to more complex discourse-level functions. There are no studies reported on pragmatic functions of code-switching in Indian languages. Present study focuses to look at: the discourse functions of code-switching among normal Kannada-English & Malayalam-English bilingual adults. 6 Kannada-English & 6 Malayalam-English bilingual speakers were taken. Speech samples were recorded, transcribed and studied for the presence of differentcode-switching patterns such as; inter-sentential code-switching, intra-sentential code-switching, tag switching and borrowing. Results revealed subjects with Malayalam as their L1 showed intra-sentential code switching for about 82 times, borrowing occurred 16 times, inter-sentential code switching was observed 4 times and tag switching occurred only once. Similarly, in subjects with Kannada as their L1, intra-sentential code-switching was seen 100 times, borrowing occurred 14 times and tag switching 4 times. Inter-sentential code switching was absent. Intra-sentential code-switching is commonly seen among the subjects followed by borrowing, tag-switching andinter-sentential switching. These types of switching to L2 could be due to the English educational background of subjects, linguistic motivation, lack of technical terms in native languages, also the fact that English might express the message better. Hence, present study contributes to a better understanding of code-switching as a bilingual phenomenon in general and also gives an overview of Kannada-English & Malayalam-English bilingualism. In order to validate these results,more number of bilinguals has to be studied across various Indian languages.